Adoption of a combined assurance framework in South Africa’s provincial government departments: A compliance case study - Dubihlela, Jobo; Solomon, Henoacia (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
This paper examines the role of compliance units in the adoption of a combined assurance framework within provincial government departments in the Western Cape. It strives to avoid risks being managed in silos and ensure risks are efficiently managed collaboratively. A combined assurance framework provides a coordinated approach to all assurance activities. It aims to optimise the assurance coverage obtained from management and internal and external assurance providers on the risk areas affecting an organisation. Compliance is an independent function that supervises and participates in placing internal procedures in conformity with regulations within the context of the integrity policy covering fields such as corporate governance and fields possibly required by respective Boards of Directors, taking account of risks in various activities. This study followed a qualitative approach, and data was collected by interviewing various officials within the provincial government departments. A sample of 10 respondents ranging from CAEs, Internal Auditors, and Directors was selected to participate in the face-to-face semi-structured interviews. The study aimed to conclude that a combined assurance framework undeniably incorporates the efforts of management and external and internal assurance providers. It builds their alliance and develops a combined and more holistic breakdown of the organisation's risk profile. The general view is that the assurance gap is significant. However, the combined assurance framework will furnish a clear process and criteria for recognising each department's assurance gap and degree of risk coverage.